Fatal cerebral malaria: a venous efflux problem - Frevert, Ute; Nacer, Adéla (Frontiers in Cellular and Infection Microbiology, 2014)
Most Plasmodium falciparum-infected children with cerebral malaria (CM) die from respiratory arrest, but the underlying pathology is unclear. Here we present a model in which the ultimate cause of death from CM is severe intracranial hypertension. Dynamic imaging of mice infected with P. berghei ANKA, an accepted model for experimental CM, revealed that leukocyte adhesion impairs the venous blood flow by reducing the functional lumen of postcapillary venules. The resulting increase in intracranial pressure exacerbates cerebral edema formation, a hallmark of both murine and pediatric CM. We propose that two entirely different pathogenetic mechanisms – cytoadherence of P. falciparum-infected erythrocytes in pediatric CM and leukocyte arrest in murine CM – result in the same pathological outcome: a severe increase in intracranial pressure leading to brainstem herniation and death from respiratory arrest. The intracranial hypertension model unifies previous hypotheses, applies to human and experimental CM alike, eliminates the need to explain any selective recognition mechanism Plasmodium might use to target multiple sensitive sites in the brain, and explains how an intravascular parasite can cause so much neuronal dysfunction.